2019
DOI: 10.7554/elife.46207
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic lateral interactions drive ESCRT-III heteropolymer assembly

Abstract: Self-assembly of ESCRT-III complex is a critical step in all ESCRT-dependent events. ESCRT-III hetero-polymers adopt variable architectures, but the mechanisms of inter-subunit recognition in these hetero-polymers to create flexible architectures remain unclear. We demonstrate in vivo and in vitro that the Saccharomyces cerevisiae ESCRT-III subunit Snf7 uses a conserved acidic helix to recruit its partner Vps24. Charge-inversion mutations in this helix inhibit Snf7-Vps24 lateral interactions in the polymer, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 56 publications
8
58
0
Order By: Relevance
“…On the cylindrical surface, the neighboring rings on the spiral are stabilized by the interaction of helix 4 of one ring with the long helix of adjacent ring. The same type of electrostatic interaction has been recently confirmed in the hetero‐polymer of Snf7 with the ESCRTIII subunit Vps24 . The energetic properties of these preformed spirals are reported in Table .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…On the cylindrical surface, the neighboring rings on the spiral are stabilized by the interaction of helix 4 of one ring with the long helix of adjacent ring. The same type of electrostatic interaction has been recently confirmed in the hetero‐polymer of Snf7 with the ESCRTIII subunit Vps24 . The energetic properties of these preformed spirals are reported in Table .…”
Section: Resultssupporting
confidence: 69%
“…This explains the experimental finding that helix 4 is necessary for helical oligomer formation. The same type of interaction and its importance for membrane tubulation has recently been highlighted in the Snf7‐Vps24 hetero polymer …”
Section: Discussionsupporting
confidence: 55%
“…In the experiments analyzing the number of strands per filament ( Figures 1C and S1E), in comparison to data from Mierzwa et al (2017), higher concentrations and longer incubation times of Vps2-Vps24 were used to ensure comparability with the experiments including Vps2-Did2, for which high concentration and long incubation were required due to its low affinity for Snf7. High concentration and long incubation of Vps2-Vps24 result in increased filament bundling a phenomena we (data not shown) and other using different ESCRT-III filaments (Banjade et al, 2019) observed previously. However, the clear prevalence of multimer-of-2 strands per filament strongly indicates the occurrence of the lateral co-polymerization we described in Mierzwa et al (2017).…”
Section: Electron Microscopysupporting
confidence: 80%
“…Thus, interactions between the j and j+1 subunits along the IST1 strand provide the force that flexes the CHMP1B elbow and consequently constricts and elongates the filament. These sliding, lateral interactions to promote changes in filament architecture have also been observed for the yeast ESCRT-III proteins Snf7 and Vps24 ( 38 ).…”
Section: Resultsmentioning
confidence: 53%